Electrochemical Methane Conversion. Issue 9 (17th July 2021) - Wang, Qihao; Kan, Miao; Han, Qing; Zheng, Gengfeng
Abstract : Methane, as an earth‐abundant C1 resource, is a greenhouse gas as well as a key building block in the chemical industry. Electrochemical conversion of methane into fuels and valuable chemicals represents an attractive promise toward carbon neutralization and reducing CO2 emission in industrial methane reforming. To overcome the catalyst degradation and energy cost problems, it is critical to activate the CH bonds in methane effectively to operate under ambient conditions, while without the cost of product selectivity. This review focuses on catalyst structures and system design strategies in recent developments of electrocatalytic methane conversion progresses. The combination of electro‐, thermo‐, and photocatalytic methods can enable complementary and enhanced activities, as well as new insights in reaction conditions and mechanisms. Abstract : Electrochemical conversion of methane into fuels and valuable chemicals represents an attractive promise toward carbon neutralization and reducing carbon dioxide emission in methane reforming. The combination of electro‐, thermo‐, and photocatalytic methods can enable complementary and enhanced activities as well as new insights in reaction conditions and mechanisms.